An Investigation of Hand-Drawn Representations of Rivers by Fifth-Grade Students in Greek Elementary Schools. (4th March 2014) - Galani, Apostolia; Rokka, Ageliki
Abstract : This paper is part of a wider study and reflects an attempt to explore the cognitive representations that Greek pupils in the 5th grade of elementary school have, as they emerge from the freehand drawing of rivers. An attempt was made to explore the extent to which the cognitive representation skills of school pupils are associated with real images of space and the extent to which intervention by the teacher who presents the structure of a river emphasizing on how it is formed can contribute to an improvement in the drawings made. Two groups of pupils (n = 125, n = 113 ) took part in this study. They were taught one of two parallel lesson plans, to create representations relating to the concept of river. This was followed by an analysis of the drawings and the pre- and postteaching interviews (n = 60 /group). The results indicate that pupils perceive the differences between reality and how it is conveyed in images, and they reproduce stereotypical models of rivers presented in schoolbooks without using complex structures to represent them. In addition, it was clear how encouraging use of children's mental maps can be not only in revising existing teaching theories but also in building new ones.